DESCRIPTION OF COPING STRESS S IN TEACHERS WHO TEACH SPECIAL NEEDS IN SDS WOODLANDS MONTESSORI - Poespitarini, Farida; Natalia,; Asmi Rozali, Yuli; Z. Supri, Ida (International Journal of Psychosocial Rehabilitation, 2020)
Children with special needs who attend SDS Woodlands Montessori are a source of stress for their teachers. In addition, the high demands of work from the school and parents of students can add to the feeling of stress on teachers of children with special needs. To deal with stress, the ability to overcome it is needed, which is called Coping Stress. This study aims to see Coping Stress in teachers who teach children with special needs at SDS Woodlands Montessori. The design of this study is quantitative descriptive, which uses saturated sampling techniques. With a total sample of 25 teachers at SDS Woodlands Montessori. The reliability level of the Coping Stress data analysis tool is (α) = 0.920 with 28 valid items. From the results of statistical tests, it was found that out of 25 SDS Woodlands Montessori teachers, more were using Coping Emotion-focused coping stresses were 52%, compared to teachers who had problem-focused coping by 48%. In this study there was no association between stress coping with education, age and gender. Other findings in this study showed that teachers in early adulthood used more emotion-focused coping while teachers in middle adulthood all used problem-focused coping.